Clinical utility of the BioFire FilmArray Blood Culture Identification panel in the adjustment of empiric antimicrobial therapy in the critically ill septic patient. - Roxanne Rule; Fathima Paruk; Piet Becker; Matthew Neuhoff; Julian Chausse; Mohamed Said (PLoS ONE)
Sepsis and septic shock are key contributors to mortality in critically ill patients and thus prompt recognition and management thereof is central to achieving improved patient outcomes. Early initiation of appropriate antimicrobial therapy constitutes a crucial component of the management strategy and thus early identification of the causative pathogen is essential in informing antimicrobial therapeutic choices. The BioFire FilmArray blood culture identification (BCID) panel is a US Food and Drug Administration (FDA) approved rapid, multiplex polymerase chain reaction assay for use on positive blood cultures. This study evaluated its clinical utility in the intensive care unit (ICU) setting, in terms of amendment of empiric antimicrobial therapy in critically ill patients with sepsis. The assay proved useful in this setting as final results were made available to clinicians significantly earlier than with conventional culture methods. This, in turn, allowed for modification of empirical antimicrobial therapy to more appropriate agents in 32% of patients. Additionally, the use of the BioFire FilmArray BCID panel permitted the prompt implementation of additional infection prevention and control practices in a sizeable proportion (14%) of patients in the study who were harbouring multidrug resistant pathogens. These findings support the use of the BioFire FilmArray BCID panel as a valuable adjunct to conventional culture methods for the diagnosis and subsequent management of critically ill patients with sepsis.